Effectiveness of Deferred Combined Androgen Blockade Therapy Predicts Efficacy in Abiraterone Acetate Treated Metastatic Castration-Resistant Prostate Cancer Patients after Docetaxel - Li, Jian-Ri; Chiu, Kun-Yuan; Wang, Shian-Shiang; Yang, Cheng-Kuang; Chen, Chuan-Shu; Ho, Hao-Chung; Hung, Chi-Feng; Cheng, Chen-Li; Yang, Chi-Rei; Chen, Cheng-Che; Wang, Shu-Chi; Lin, Chia-Yen; et al. (Frontiers in Pharmacology, 2017)
Introduction Conventional anti-androgen regimens were widely used as an initiation or combined androgen blockade (CAB) therapy in advanced prostate cancer patients. Currently, new androgen pathway inhibitors such as abiraterone acetate (AA) and enzalutamide had been proven effective in metastatic castration resistant prostate cancer. In this study, we attempt to analyze the role of conventional anti-androgen drugs as deferred CAB therapy in castration-resistant prostate cancer patients. Materials and Methods. From 2012 to 2017, 48 metastatic castration-resistant prostate cancer (CRPC) patients who received sequential treatments with primary androgen blockade, oral anti-androgen regimens, and docetaxel followed by AA treatment were included. We defined effective deferred CAB as any decline of PSA after add-on antiandrogen after CRPC. Patients were separated into effective and ineffective deferred CAB. Comparison between two groups in the first line androgen deprivation therapy duration, CRPC PSA level, pre-AA PSA level, chemotherapy dosages, duration, and patients progression free survival and overall survival after AA treatment were analyzed. Results Twenty-three patients (47.9%) achieved PSA decline after deferred CAB. Among total 48 patients, 24 patients experienced PSA decline more than 50% after AA treatment. The median PSA progression-free survival and overall survival after AA treatment in the total cohort of 48 patients were 4.4 and 24.3 months, respectively. The effective deferred CAB group showed significantly lower PSA level, lower percentage of PSA progression, higher total follow-up duration, higher percentage of surviving patients, better progression free survival and overall survival estimate after AA treatment. Of the eight variables analyzed, effectiveness in deferred CAB showed positive association to progression free survival (HR 0.29, 95% CI 0.12-0.67, p= 0.004) and overall survival (HR 0.24, 95% CI 0.07-0.81, p= 0.022). First line androgen deprivation therapy (ADT) duration also showed positive association to overall survival (HR 0.95, 95% CI 0.91-0.99, p= 0.023). Conclusions Effectiveness of deferred CAB therapy was positively associated with progression free survival and overall survival of AA treatment after docetaxel. It can be used as a pre-treatment predictor.